LATIN AMERICAN DEMOCRACIES UNDER THE THREAT OF INEQUALITY (Andamios, Revista de Investigación Social, 2010)
Democratic transition in Latin America has made an important progress in the last twenty years. However, strong social deficits persist all over the region. This article intends to analyze the role of inequality in the democracies of Latin American subcontinent.
Keywords: Democracy; Latin America; inequality; corruption; violence